Chrononutrition Behaviors, Sugar-sweetened Beverage Consumption, Sleep Quality and the Association with Body Mass Index Among Malaysian Women - Nur Islami Mohd Fahmi Teng; Juliana Norsham; Aina Nadhra; Aimi Dalila; Nursyafiqa; Siti Iylia Nasuha; Srijit Das (Taylor & Francis Online, 2024)
Indexed by Scopus